Improvement of the efficiency of booth multiplier - Siva Kumar, M; Kumar Tulasi, Sanath; Srinivasulu, N; Krishnam Naidu Yedla, G S; Raghuveer, E; Hari Kishore, K (International Journal of Engineering and Technology, 2017)
Objective: To Improve the performance of Booth Multiplier and reduce power consumption.Method: The most essential form of multiplication consists of framing the result of two unsigned (positive) binary numbers.Finding: Booth Multiplier consists of pre-defined table. According to this algorithm, multiplication of two numbers x and y (x*y) is same as multiplication of y and x (y*x). At times this rule fails due to which we modify the logic by converting the decimal number in to 4 bit binary number and appending (n-2) zeros at most significant bit and one zero at least significant bit.Improvement: By using this method we can get accurate results in multiplication by multiplying like (x*y) andÂ Â Â (y*x).